Enterococcus faecium GEFA01 alleviates hypercholesterolemia by promoting reverse cholesterol transportation via modulating the gut microbiota-SCFA axis - Xu, Wenfeng; Zou, Kaixiang; Zhan, Ying; Cai, Yunjie; Zhang, Zhihong; Tao, Xueying; Qiu, Liang; Wei, Hua (Frontiers in Nutrition, 2022)
The aim of this study is to identify cholesterol-lowering commensal strains from healthy lean individual and to evaluate cholesterol-lowering capacity of Enterococcus faecium GEFA01 in mice fed with a high cholesterol and fat diet. Enterococcus faecium GEFA01 was isolated from the stool of a healthy lean individual on a selective basal salt medium supplemented with cholesterol. Enterococcus faecium GEFA01 exhibited a cholesterol removal rate of 46.13% by co-precipitation, assimilation, and degradation of cholesterol. Moreover, Enterococcus faecium GEFA01 significantly decreased the body weight of mice, serum TC (total cholesterol) and LDL-C (low-density-lipoprotein cholesterol) levels, and hepatic TC, TG (triglycerides) and LDL-C levels, and increased serum HDL-C (high-density-lipoprotein cholesterol) levels in mice fed with a high-cholesterol diet compared with the HCD group. We also observed that Enterococcus faecium GEFA01 significantly down-regulated the gene expression of Hmgcr, Srebp-1c, Fxr, Shp and Fgf15, and up-regulated the gene expression of Ldlr, Abcg5/8, Abca1, Cyp7a1 and Lxr in the liver of mice in relative to HCD group, and markedly increased the relative abundances of Lactobacillus, Akkermansia, Bifidobacterium and Roseburia, but decreased the abundance of Helicobacter in the feces. Collectively, we confirmed that Enterococcus faecium GEFA01 exhibited cholesterol-lowering effects in mice fed a high-cholesterol diet, which was achieved by assimilation, co-precipitation, and degradation of cholesterol, and by modulating gut microbiota-SCFAs axis that promoted reverse cholesterol transport and excretion of bile acid. Our study demonstrated that Enterococcus faecium GEFA01 may be used as a probiotic candidate for lowering cholesterol levels in the future.